Belief in Karma: The Belief-Inducing Power of a Collection of Ideas and Practices with a Long History - Lehtonen, Tommi (Religions, 2023)
This article provides an analysis of the concept of karma and related concepts, such as rebirth, merit, and transfer of merit, along with a historical survey focusing on classical texts. The attractiveness of the belief in karma lies in two main reasons. The first is the moral ideal of getting one’s just deserts on the basis of one’s actions and omissions. The second reason involves the idea of rebirth. The belief in both karma and rebirth can bring consolation with the hope of life hereafter, where one’s destiny is determined not by chance, but by the moral quality of one’s actions in this or previous lives. The belief in karma also incorporates diverging elements, such as transfer of merit. The practice of transfer of merit serves to improve an individual’s moral and religious status through rituals or other suitable means, while the doctrine of karma itself strongly speaks to the strict fulfilment of retributive justice. Both motives—fulfilling justice according to the law of karma and improving one’s moral status through transfer of merit—are psychologically powerful and attractive, although their mutual compatibility is debatable.